Prevalência do transtorno depressivo maior em pacientes com Hepatite C crônica e características psicométricas de instrumentos diagnósticos para o rastreamento de quadros depressivos - Renato Ferreira Araújo (2012)
Introduction: Hepatitis C is an important public health problem in Brazil and in the rest of the world. It is estimated that 130 million to 170 million people are infected by hepatitis C virus (HCV) in the world. In addition to the hepatic manifestations, various extrahepatic manifestations are common and occur in up to 40% of patients, including neuropsychiatric symptoms. Objective: To evaluate the prevalence of psychiatric comorbidities in patients with hepatitis C, with emphasis on major depressive disorder (MDD) in patients treated in a Reference Center for Viral Hepatitis - Viral Hepatitis Clinic of the Alfa Institute of Gastroenterology, Hospital of the Universidade Federal de Minas Gerais. To evaluate the psychometric properties of HADS and HDRS scales for the diagnosis and screening of depression in patients with chronic hepatitis C. Methodology: the period between February 2010 to December 2011 were included prospectively 134 patients with chronic hepatitis C patients (57 males and 77 females) the identification of psychiatric disorders, especially MDD, was made by means of structured interviews MINI Plus v 5.0.0. We compared clinical, laboratory and associated sociodemographic groups of patients with and without depression, evaluating also the reliability and internal consistency of the HADS depression and HDRS. Results: The mean age of patients encompassed in the study was 53 ± 11 years. The median time from diagnosis of HCV infection was 23 ± 10.1 years. At the time of evaluation, 69 patients (53.1%), had clinical comorbidity. The most common psychiatric disorder in patients with chronic hepatitis C was MDD (n = 41, 30.6%), followed by anxiety disorders: generalized anxiety disorder (n = 11, 8.2%) and panic disorder (n = 4, 3.0%).In multivariate analysis, factors that correlated with major depressive disorder were: history of MDD in the past (PR = 2), anxiety disorders (PR = 2.5) and diabetes (PR = 1.9). Age> 60 years proved to be a protective factor (PR = 0.35). The subscale (HAD)-D showed good agreement (Kappa = 0.639) and area under the ROC curve of 0.903. The HAD-A subscale showed fair agreement (Kappa = 0.540) and area under the ROC curve of 0.859. Both subscales showed low sensitivity (67.6 and 56.7%, respectively) and high specificity (93.2%), with cutoff 8. The HDRS scale showed good agreement (Kappa = 0.664) and area under the ROC excellent (0.931). The sensitivity and specificity were respectively 91.9% and 80.0%. The cutoff point with the best sensitivity / specificity according to ROC curve analysis was 6. Conclusion: MDD was the most frequent psychiatric diagnosis in patients with chronic hepatitis C and is significantly associated with anxiety disorders, diabetes and previous history of MDD. The HDRS scales and HADS showed good agreement with the diagnosis of MDD. The HDRS might be of interest in clinical research, but has as impediment to rely on an appraiser with expertise in mood disorders. The HADS scale, despite its low sensitivity, has more applicability in the clinical setting because it is short duration and to be self administered.